Trade liberalization in low income economies. time inconsistency and fiscal policy. Francesco Daveri - Daveri, Francesco; International Development Centre, Centro Studi Luca d'Agliano (Italia) (Torino, Italia : International Development Centre, 1990)
Considera un caso de intervención gubernamental, promocionando la industrialización y la política industrial
Keywords: COMERCIO EXTERIOR; INDUSTRIA; POLÍTICA COMERCIAL